Foreignization and domestication in translating Louise Glück’s poems: An ideological analysis - Sarrohmahniyati Sarrohmahniyati; Aidil Syah Putra; Eka Ugi Sutikno (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
This study examines how translation techniques interact with ideological orientation in the Indonesian rendering of selected poems from Firstborn by Louise Glück. It integrates Lawrence Venuti's concepts of foreignization and domestication with the taxonomy of translation techniques proposed by Lucía Molina and Amparo Hurtado Albir. Adopting a qualitative design grounded in comparative textual analysis, the dataset comprises 21 translation units drawn from five poems, along with their Indonesian versions published on Buruan.co. The findings indicate that literal translation and borrowing tend to align with a foreignizing orientation, as they preserve stylistic features and cultural markers of the source text. In contrast, techniques such as adaptation, modulation, amplification, reduction, and transposition are more closely associated with domestication, facilitating readability and cultural accessibility for the target audience. Overall, the distribution reflects a relatively balanced pattern, though it leans slightly toward domestication, particularly in instances where semantic clarity and reader comprehension are prioritized. By grounding ideological tendencies in observable textual evidence, this study contributes to translation studies by linking macro-level theoretical constructs (ideologies) with micro-level analytical practice (techniques). It also provides practical insights for translators seeking to negotiate the tension between aesthetic fidelity and readability in the translation of contemporary poetry.